La formación continua de los docentes de educación básica infantil en américa latina: una revisión sistemática - Aguirre-Canales, Vilma I. (2021)
The main purpose of this article was to carry out a systematic review of empirical studies on the continuous training of teachers at the levels of basic early childhood education in Latin America, this information was collected from journals indexed in relation to the subject in the database of Scielo, Scopus, Ebsco and Dialnet, between the years 2010 to 2019. According to the analysis of the collected evidence, aspects such as: a) continuous training as a means of transforming pedagogical practice, b) teacher professional development and research culture as part of continuous training, c) the importance of developing continuous training programs to enhance the pedagogical capacities of teachers. Concluding that the publications in relation to continuous training present an ascending character, with Brazil being the country with the highest number of publications. Likewise, it was revealed that the methodology most used in these studies is of a qualitative approach and finally it was shown that the applications of continuous training programs had positive effects on the modification of their daily work as a teacher and improvement as a professional.